EVALUASI PENERAPAN PENGUNGKAPAN INFORMASI ASET KEUANGAN MENURUT PSAK 60 PADA PT. BANK NEGARA INDONESIA (PERSERO) TBK - Pangkey, Zwingly Juliano Stefanus; Kalangi, Lintje; Lambey, Robert (GOING CONCERN : JURNAL RISET AKUNTANSI, 2016)
Financial Assets is one of the factors that really support banking company's business. Statement of Financial Accounting Standards (SFAS) No. 60 about Financial Assets: disclosure head for organize entities to giving disclosure in their financial statements which enable the users to evaluate the significance of financial instruments to the position and financial performance of the entity, characteristic, and risk scope which apeear from financial instruments which the entity’s exposed during period and in the end of reporting period, and how the entity managing the risk. The object of this research is PT. Bank Negara Indonesia (Persero) Tbk. with  financial statements and notes to the financial statements of December 31, 2014 and 2015 as sample. The data analysis method used in this study is a qualitative method. From the research, the results that can be concluded about the application of financial assets information disclosure  at PT. Bank Negara Indonesia (Persero) Tbk. is appropriate  with Statement of Financial Accounting Standards (SFAS) No. 48 about financial assets: disclosure but not yet revealing about values related to offsets and about default. Expected in the  future PT. Bank Negara Indonesia (Persero) Tbk. could add disclosure about offsetting values and default. . Keyword : Bank, Financial Assets, Disclosure, Financial Instrument